2020
DOI: 10.1002/ajae.12038
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Premium Payment, Insurance Adoption, and Household Investment in Rural China

Abstract: We conduct a randomized controlled trial to examine the impacts of delayed premium payment on insurance uptake and the subsequent investment decisions among smallholder farmers in rural China. Our results show uptake among those with the delayed payment option is 10% higher than and three times as high as among those without the option. We also find a positive impact of delayed premium payment and insurance adoption on household investment in production, especially higher risk activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Notwithstanding, there is large withincountry heterogeneity that is far larger than any between-country differences. Anecdotal evidence on time preferences of farmers in developing countries (note that we have not reviewed this literature systematically) (e.g., Alemayehu et al, 2019;Fischer & Wollni, 2018;Kramer & Kunst, 2020) and Asia (e.g., Liu et al, 2020;Mao et al, 2021;Sarwosri & Mußhoff, 2020), show often lower time preferences than revealed in the studies for Europe and North America. For example, subsistence farmers often have elicited discount rates below 10% (e.g., the cattle herders in Mali and Burkina Faso surveyed by Liebenehm and Waibel [2014]).…”
Section: Discussionmentioning
confidence: 80%
“…Notwithstanding, there is large withincountry heterogeneity that is far larger than any between-country differences. Anecdotal evidence on time preferences of farmers in developing countries (note that we have not reviewed this literature systematically) (e.g., Alemayehu et al, 2019;Fischer & Wollni, 2018;Kramer & Kunst, 2020) and Asia (e.g., Liu et al, 2020;Mao et al, 2021;Sarwosri & Mußhoff, 2020), show often lower time preferences than revealed in the studies for Europe and North America. For example, subsistence farmers often have elicited discount rates below 10% (e.g., the cattle herders in Mali and Burkina Faso surveyed by Liebenehm and Waibel [2014]).…”
Section: Discussionmentioning
confidence: 80%
“…Insurance is an intangible ‘credence’ good (Gaurav et al, 2011). Lack of trust in the formal financial system has been previously recognised as the most important barrier preventing individuals from insurance adoption (Cole et al, 2013; Giné et al, 2008; Liu et al, 2020). It is particularly relevant in China where legal protections are weaker and financial education level are lower (Cai et al, 2009; Liu et al, 2020; Wang et al, 2021).…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Through a drought insurance experiment in Ethiopia, Belissa et al (2019) find that postponed premium payment enhances insurance take-up substantially. Likewise, through a field experiment in China, Liu et al (2020) find that allowing farmers to defer premium payment leads to more insurance purchase.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations